2011
DOI: 10.1093/brain/awq367
|View full text |Cite
|
Sign up to set email alerts
|

The sigma-1 receptor enhances brain plasticity and functional recovery after experimental stroke

Abstract: Stroke leads to brain damage with subsequent slow and incomplete recovery of lost brain functions. Enriched housing of stroke-injured rats provides multi-modal sensorimotor stimulation, which improves recovery, although the specific mechanisms involved have not been identified. In rats housed in an enriched environment for two weeks after permanent middle cerebral artery occlusion, we found increased sigma-1 receptor expression in peri-infarct areas. Treatment of rats subjected to permanent or transient middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 58 publications
8
128
3
Order By: Relevance
“…Only animals that were not able to cross the rotating pole were randomly assigned into treatment groups. 15 Subsequently, starting on day 2 after pMCAO, rats were housed in standard laboratory cages or EE cages for 3 days. Neurologic score was assessed by the rotating pole test at postoperative day 5 as described previously 14 and brain tissue from the same set of animals has been used for analyses in the present study.…”
Section: Randomization and Treatment Protocolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only animals that were not able to cross the rotating pole were randomly assigned into treatment groups. 15 Subsequently, starting on day 2 after pMCAO, rats were housed in standard laboratory cages or EE cages for 3 days. Neurologic score was assessed by the rotating pole test at postoperative day 5 as described previously 14 and brain tissue from the same set of animals has been used for analyses in the present study.…”
Section: Randomization and Treatment Protocolsmentioning
confidence: 99%
“…Neurologic function was assessed by the rotating pole test that measures coordination and integration of movement and has been described previously. 15 Infarct volumes were determined as decribed previously. 14 …”
Section: Post Stroke Housing Conditions-enriched Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Sigma-1R activation was reported to induce neuronal re-growth and functional recovery following experimental stroke in a rat model [189] and a phase II trial was conducted with the Sigma-1R agonist cutamesine (SA4503) in patients with ischemic stroke [190]. A recent study showed that another Sigma-1R agonist, PRE084, improved behavioral symptoms in a Parkinson's disease mouse model [191].…”
Section: Therapeutic Targetingmentioning
confidence: 99%
“…A model has been proposed in which the sigma-1 receptors are "silent" under normal physiological conditions, whereas in disease, the receptor behaves as a chaperone that binds 'client' proteins, modulates cellular activity and promotes survival (Su et al 2010). This hypothesis has received some support from studies demonstrating that sigma-1 silencing would suppress recovery after experimental stroke (Ruscher et al 2011) and promote retinal degeneration after acute damage to the optic nerve (Mavlyutov et al 2012).…”
mentioning
confidence: 99%